Identifikasi Waste dengan Pendekatan Value Stream Mapping (VSM) di CV. DS - Emmy Nurhayati (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
Waste in an activity is a process that does not add value to the company. CV. DS produces various kinds of gloves and motorcycle riding equipment as well as outdoor equipment, in the production process waste is found, especially in the sewing section. The purpose of identifying waste through lean manufacturing is to increase customer value through continuous improvement through the value-to-waste ratio. The loss of waste can increase the effectiveness of the production line which can have an impact on increasing production output. The method used in the identification of waste is the Value Stream Mapping (VSM) approach through the Current State Map (CSM) and Future State Map (FSM). The results obtained indicate that 5 types of waste that occur, namely defects, inappropriate processing, excessive transportation, waiting, and unnecessary motion. In addition, it also obtained results in the form of a reduction in production lead time by 68.54 minutes and non-value added activities reduced by 68 minutes. This is expected to increase production output per day.